740 CAMRELIZUMAB IN COMBINATION WITH PREOPERATIVE CHEMOTHERAPY FOR LOCALLY ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A SINGLE-ARM, OPEN-LABEL, PHASE II STUDY. (17th September 2021) - Wang, Feng; Qi, Yu; Meng, Xiangrui; Fan, Qingxia
Abstract:  : At present, ESCC has a dismal prognosis with huge unmet clinical needs. With the potential benefit of combining PD-1 inhibitor with nCT, we conducted a phase II trial to assess the efficacy and safety of Camrelizumab plus nCT for locally advanced ESCC. Methods: 45 patients (pts) with histologically confirmed stage II/III/IVa(cT2-4aN0-3 M0) ESCC were enrolled from February 2020 to March 2021.The study was divided into two stages, stage1: we administered 1 cycle of Camrelizumab for induction therapy (200 mg q2 weeks); stage2: pts received 2 cycle of Camrelizumab (200 mg every 3 weeks) plus docetaxel and nedaplatin, followed by surgery within 4 ~ 6 weeks after neoadjuvant therapy completion. Primary endpoint was major pathologic response (MPR). Secondary endpoints included pathologic complete response (pCR), R0 resection rate, disease-free survival (DFS) and overall survival (OS). Results: At the cutoff date of Mar 9, 2021, 45 eligible pts were enrolled, neoadjuvant treatment was completed in 39 pts. Thus far 32 pts were resected, all patients underwent an R0 resection. Postoperative pathology showed that TNM stage decreased in 28 pts with 87.5% reduction rate. 19 pts (59.38%) reached major pathologic response, 9 pts (28.13%) reached pathologic complete response (no surgery related mortality). A total of 75.56% had AEs with 13.33% of grade ≥ 3 AEs. Date for median DFS and OS were not matured. Conclusion: Camrelizumab in combination with preoperative chemotherapy followed by surgery for locally advanced ESCC showed promising downstaging effect and MPR with good tolerance, and its efficacy and safety could be further studied in later trials. Clinical trial information: NCT03917966.